The 2nd International Babylon Conference on Clinical and Experimental Pharmacological Research: focusing on drug development and repurposing, drug safety, and public health - Zarros, Apostolos (Pharmakeftiki, 2025)
The proceedings of the 2nd International Babylon Conference on Clinical and Experimental Pharmacological Research (taking place at the College of Pharmacy of the University of Babylon, in Hillah, Iraq; April 19-20, 2025) are hereby hosted by Pharmakeftiki; a journal founded by the Hellenic Society of Medicinal Chemistry (HSMC) in 1988 and currently published independently with the support of both the HSMC and the Hellenic Pharmaceutical Society. This year’s conference proceedings are more extensive in terms of both the number of papers included in them and the thematic representation of the field. In that respect, the conference’s scientific programme exhibits an encouraging enrichment that also signifies the importance of this event for the Iraqi pharmacological community. The proceedings cover the main messages of the keynote speakers’ talks, present the findings of a large number of clinical, epidemiological, and experimental research studies, and also host interesting (mini-)reviews on important pharmacological topics that, in most cases, are penned by postgraduate students and their supervisors, as part of their degree prerequisites. The conference’s committees have successfully established an international forum for the discussion of critical developments in pharmacological research, with this year’s conference focusing on drug development and repurposing, drug safety, and public health.